Depressive symptoms in children and adolescents with epilepsy and primary headache: a cross-sectional observational study - Pastorino, Grazia Maria Giovanna; Olivieri, Miriam; Viggiano, Andrea; Meccariello, Rosaria; Roccella, Michele; Parisi, Lucia; Cerulli Irelli, Emanuele; Di Bonaventura, Carlo; Orsini, Alessandro; Operto, Francesca F. (Frontiers in Neurology, 2024)
1) Background: The primary aims of our cross-sectional observational study were: (I) to determine the prevalence of depressive symptoms in children and adolescents with epilepsy compared to controls and (II) to explore the difference in depressive symptoms in patients with epilepsy only and those with epilepsy and primary headache in comorbidity. The secondary objective was to explore parental stress level.(2) Methods: 68 pediatric patients aged 6-18 years (44 with epilepsy only and 24 with epilepsy and headache) and 50 controls were recruited. Depressive profile and parental stress were assessed using Children's Depression Inventory, Second Edition (CDI-2) and Parenting Stress Index-Short Form (PSI-SF). (3) Results: The group with epilepsy showed significantly high depressive symptoms and parental stress compared to controls. The patients with headache in comorbidity experienced more depressive symptoms than those with epilepsy only.(4) Conclusions: Depressive symptoms are more prevalent in patients who have comorbid epilepsy and primary headache, therefore the neurological/psychological mechanisms underlying this condition should be further investigated. The simultaneous presence of epilepsy, headache and depressive symptoms impacts the quality of life of patients and their parents, increasing parental stress and family management.